Nanomaterials composites for thermal management of small satellites - Yeo, Kirby Ker Bi (Nanyang Technological University, 2024)
This report examines the thermal management properties of novel carbon nanomaterials-phase change material composites (CN-PCM) for applications in small satellite systems. By the synthesis of various composites (i.e. graphene foam), this report evaluates the thermal management properties for more efficient temperature regulation in a small satellite electronics system. The findings from the project showed that the synthesised graphene foam was able to regulate temperature within safe operating ranges of the electronics when exposed to higher temperature. Furthermore, when compared to the regulation of temperature without the composite, it shows that with the CN-PCM added, the time taken for the temperature to reach a reference temperature was longer when compared to the same setup without the CN-PCM. It must be noted that the experiments are conducted in a controlled laboratory environment and may vary when compared to other similar experiments. With our experiments, we found that CN-PCM indeed helps to regulate heat more effectively and keep the temperature relatively lower compared to the experiment without the CN-PCM.